2023
DOI: 10.3389/fmicb.2022.1068825
|View full text |Cite
|
Sign up to set email alerts
|

Alterations and correlations of gut microbiota, fecal, and serum metabolome characteristics in a rat model of alcohol use disorder

Abstract: BackgroundGrowing evidence suggests the gut microbiota and metabolites in serum or fecal may play a key role in the process of alcohol use disorder (AUD). However, the correlations of gut microbiota and metabolites in both feces and serum in AUD subjects are not well understood.MethodsWe established a rat model of AUD by a chronic intermittent ethanol voluntary drinking procedure, then the AUD syndromes, the gut microbiota, metabolomic profiling in feces and serum of the rats were examined, and correlations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 91 publications
3
9
0
Order By: Relevance
“…29 influenced by alcohol-induced gut dysbiosis. 30 In our results, the total PE levels were significantly increased in the EF group of both male and female mice (Figure 4), but the PG and HBMP levels were decreased specifically in the male EF group. A previous study in male mice fed ethanol for 5 weeks showed decreased PGs in the liver in the EF group compared with controls.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…29 influenced by alcohol-induced gut dysbiosis. 30 In our results, the total PE levels were significantly increased in the EF group of both male and female mice (Figure 4), but the PG and HBMP levels were decreased specifically in the male EF group. A previous study in male mice fed ethanol for 5 weeks showed decreased PGs in the liver in the EF group compared with controls.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, GPs are the main integral constituents of biological membranes, which play a crucial role in cellular functions. Modulation of GPs is influenced by alcohol-induced gut dysbiosis . In our results, the total PE levels were significantly increased in the EF group of both male and female mice (Figure ), but the PG and HBMP levels were decreased specifically in the male EF group.…”
Section: Discussionsupporting
confidence: 50%
“…The analysis mainly included thawing, grinding, extraction, vacuum drying of fecal samples, etc. The detailed steps are following the reference and our previous study [35,36] and in Supplementary Materials.…”
Section: Untargeted Metabolomics Analysismentioning
confidence: 99%
“…Screening criteria for differential metabolites were set as FC > 2, P < 0.05, and VIP > 1. These parameters align harmoniously with those utilized in analogous research endeavors [ 26 ]. The differential metabolites of significant KEGG pathway enrichment were calculated utilizing a hypergeometric distribution test.…”
Section: Methodsmentioning
confidence: 76%